Analisis Efektivitas Konten Dalam Meningkatkan Citra Perusahaan PT X - Reza Yusuf Ahsan (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Abstrak. This study arose from the need to understand the role of digital content in building a corporate image in the era of social media. The focus of this study is to evaluate the impact of content on improving the image of PT X. The method applied is a qualitative approach using case studies, through in-depth interviews with four key informants and direct observation in the company area. The results of the study indicate that content that is always consistent, relevant, and able to create emotional interactions with the audience has a major influence in forming a positive view of the company. However, challenges in understanding social media algorithms and low levels of content personalization present obstacles in achieving an ideal image. This study provides practical suggestions for a more efficient digital communication strategy. Keywords: Corporate Image, Content Effectiveness, Marketing Strategy, Social Media Content